Students' Perception On The Use Of WhatsApp Application As A Media For Online Learning - Muis, Latif Abdul; Syafrizal, Syafrizal; Sidik, Ezis Japar; Gailea, Nurhaeda (Journal of Linguistics, Literacy, and Pedagogy, 2024)
This study aims to investigate the perception of the use of WhatsApp applications as a medium for online learning. The researcher used a descriptive qualitative survey. Questionnaires and interviews were used as data collection techniques The objectives of the research are to know the Students’ Perceptions of the Use of WhatsApp applications as a Medium for Online Learning., and to know the benefits and difficulties of using WhatsApp applications as a media for online learning. Based on the findings and discussion, it can be concluded that the implementation of WhatsApp has advantages and disadvantages. Most of the students agreed that learning through WhatsApp is more flexible but on the other hand, they hard to understand the material.